HUBUNGAN KEBISINGAN DAN BEBAN KERJA DENGAN STRES KERJA PADA PEKERJA BAGIAN KILANG PADI - Raisha Octavariny; Wilda Wahyuni Siregar; Sri Melda Bangun; Dewi Sartika (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
In the scope of employment, work stress is a problem for the health of the workforce, has the potential to increase the risk of workplace accidents which will cause many material losses, and can reduce overall productivity. Individual conditions also affect the occurrence of work stress. This research is a quantitative analytical survey with cross sectional design. The sampling technique in this study is the Non Probability Sampling that is the Total Sampling method. Bivariate analysis is performed after the characteristics of each variable are known. Data were analyzed for bivariate calculations in this study using the Chi-square test.